Problems in organization of agrarian industry production in Serbia in transition period - Simonović, Zoran; Simonović, Dragoljub; Miletić, Slavomir (Economics of Agriculture, 2010)
The aim of this work is to highlight the problems of organizing agrarian industry production in the period of transition in Serbia. It starts from favorable natural conditions for production and it points the need for a consistent agrarian policy. Details are focused on the problem of organizing the production and on the main aspects of the process.